2023
DOI: 10.3390/molecules28114411
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fe/Ni-MOFs for the Adsorption of Ciprofloxacin from Wastewater

Abstract: This work studies the use of Fe/Ni-MOFs for the removal of ciprofloxacin (CIP) in wastewater. Fe/Ni-MOFs are prepared by the solvothermal method and characterized by X-ray diffraction (XRD), a scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT-IR), and a thermal gravimetric analyzer (TG). Under the conditions of the concentration of 50 ppm, a mass of 30 mg, and a temperature of 30 °C, the maximum adsorption capacity of ciprofloxacin removal within 5 h was 232.1 mg/g. The maximum re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…As such, MOFs are promising alternative material candidates. They are widely used for catalysis, 26,27 carbon dioxide capture, 28 antibiotics, 29,30 energy storage, 31 adsorption and separation, 32–34 drug delivery, 35 wastewater treatment, 36–40 and other functions 41–44 due to their diversified structure, higher surface area, tunable functional groups, and permanent pores. Previous studies have shown that most MOFs use a single metal ion, which is limited in the treatment of pollutants, with often poor treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…As such, MOFs are promising alternative material candidates. They are widely used for catalysis, 26,27 carbon dioxide capture, 28 antibiotics, 29,30 energy storage, 31 adsorption and separation, 32–34 drug delivery, 35 wastewater treatment, 36–40 and other functions 41–44 due to their diversified structure, higher surface area, tunable functional groups, and permanent pores. Previous studies have shown that most MOFs use a single metal ion, which is limited in the treatment of pollutants, with often poor treatment effects.…”
Section: Introductionmentioning
confidence: 99%